The Semiotics of the Peace Rituals (Pomaas Atag to Kosunayan) of Obo Manobo People - Barbosa, Estella (International Journal of Language and Literary Studies, 2022)
This study looked into the meanings of objects used in peace ritual, how these objects communicate the intention of parties involved, and how the ritual constitutes ideology on peace among the Obo Manobo people. Particularly, it is a semiotic reading of the Obo Manobo’s ritual for peace which employed Halliday’s social and functional approach to language and Lemke’s semiotic thinking. The peace ritual is found to be a semiotic system that embodies the values, symbols, and ideas of the Obo Manobos as a group. It is a multimodal communicative event that comprises various integrating elements to language, thoughts, feelings and aspirations, dramatizes collective representations, encodes the culture of the Obo Manobos and, therefore, conveys ideologies on peace. As embedded in the ritual, the Obo Manobos believe that peace is consequential effect of how they observe customary laws of the tribe, and disregarding this will result to punishment and chaos.